Geopolitical rivalries in the "common neighborhood" : Russia's conflict with the West, soft power, and neoclassical realism - Huseynov, Vasif (Soviet and post-Soviet politics and society, 2019)
This timely book analyzes 'soft power' in the light of neoclassical realist premises as part of the foreign policy toolkit of great powers to expand their sphere of influence. Vasif Huseynov argues that if nuclear-armed great powers compete against the same type of powers to expand or sustain their sphere of influence over a populated region, they use soft power as a major expansive instrument while military power remains a tool to defend themselves and back up their foreign policies. Presenting his model of soft power, the author explores the role of soft power projection by great powers in the formation of the external alignment of regional states. He focuses on the rivalries between Russia and the West (i.e. the EU and the USA) over the states located between the EU and Russia (the region known as the 'common [or shared] neighborhood') and on two of these regional states (Ukraine and Belarus) to test his hypotheses.